Molecular detection and genetic diversity of Bartonella species in large ruminants and associated ectoparasites from the Brazilian Cerrado - Gonçalves, Luiz Ricardo [UNESP]; Harrus, Shimon; Gutiérrez, Ricardo; Herrera, Heitor Miraglia; de Souza Ramos, Inalda Angélica [UNESP]; Porfírio, Grasiela Edith de Oliveira; Nachum-Biala, Yaarit; de Sousa, Keyla Carstens Marques; da Silva, Thiago Merighi Vieira [UNESP]; Campos, João Bosco Vilela; Lemos, Wagner [UNESP]; Moraes Barros-Battesti, Darci [UNESP]; et al. (Hindawi, 2020)
Currently, five Bartonella species and an expanding number of Candidatus Bartonella species have globally been reported in ruminants. Likewise, different Bartonella genotypes were identified. However, studies relating to ruminant-associated Bartonella in Brazil are scarce. The current study aimed to assess the prevalence and genetic diversity of Bartonella in cattle, buffaloes and associated ectoparasites in Brazil. For this purpose, EDTA-blood samples from 75 cattle and 101 buffaloes were sampled. Additionally, 128 Rhipicephalus microplus and one Amblyomma sculptum ticks collected from cattle, and 197 R. microplus, one A. sculptum and 170 lice (Haematopinus tuberculatus) collected from buffaloes were included. Bartonella DNA was initially screened through an HRM real-time PCR assay targeting the 16S–23S internal transcribed spacer (ITS), and the positive samples were submitted to an additional HRM assay targeting the ssrA gene. The HRM-positive amplicons were sequenced, and the nucleotide identity was assessed by BLASTn. Bartonella spp.-positive DNA samples were analysed by conventional PCR assays targeting the gltA and rpoB genes, and then, the samples were cloned. Finally, the phylogenetic positioning and the genetic diversity of clones were assessed. Overall, 21 of 75 (28%) cattle blood samples and 13 of 126 (10.3%) associated ticks were positive for Bartonella bovis. Out of 101 buffaloes, 95 lice and 188 tick DNA samples, one (1%) buffalo and four (4.2%) lice were positive for Bartonella spp. Conversely, none of the ticks obtained from buffaloes were positive for Bartonella. The Bartonella sequences from buffaloes showed identity ranging from 100% (ITS and gltA) to 94% (ssrA) with B. bovis. In contrast, the Bartonella DNA sequences from lice were identical (100%) to uncultured Bartonella sp. detected in cattle tail louse (Haematopinus quadripertusus) from Israel in all amplified genes. The present study demonstrates the prevalence of new B. bovis genotypes and a cattle lice-associated Bartonella species in large ruminants and their ectoparasites from Brazil. These findings shed light on the distribution and genetic diversity of ruminant- and ectoparasite-related Bartonella in Brazil.
Keywords: bartonellosis; buffaloes; cattle; genetic diversity; Haematopinus tuberculatus; Rhipicephalus microplus